Diversity in reproductive traits of arapaima (Arapaima spp., Müller, 1843) in Amazonian várzea floodplains: Conservation implications. Issue 2 (11th February 2019) - Gurdak, Daniel J.; Stewart, Donald J.; Castello, Leandro; Arantes, Caroline C.
Abstract: Understanding the reproductive ecology of freshwater fishes is essential to minimize the losses in global freshwater biodiversity but is often limited in data‐poor regions, such as tropical floodplain ecosystems. Specifically, the study investigated whether size at first sexual maturation and nesting features for arapaima vary within and across regions in the floodplain of the Amazon River. Data were collected at several sites in the Lower Amazon with varying arapaima densities and fishing practices. Female gonads were examined from commercial catch to calculate total length of first sexual maturation ( L 50 ). Nest features were surveyed in the field. The size at first maturation and nest features (i.e. nest morphology, habitat, and density) were compared among sites with different population densities in the Lower Amazon and among estimates drawn from the literature for other regions. In the Lower Amazon, L 50 showed significant variation between high‐density (139 cm) and other sites (~168 cm). Overall variation in L 50 estimates for arapaima range from 139 cm in the Lower Amazon to 207 cm in the Upper Amazon in Peru. Nests in different regions show variation among certain nest features and a positive relationship between nest density and arapaima population density. In the Lower Amazon, 90% of nests were found under woody vegetation. The results show considerable diversity in size at first maturity and nesting features for arapaima. This suggests that there may be multiple evolutionarily significant units or species, even within the study area. This study also illustrates the importance of forest cover to arapaima spawning. Furthermore, different nesting morphologies were found at different sites. There are meaningful variations in arapaima reproductive behaviour, both locally and basin‐wide, that require further study as they have implications for effective management and conservation initiatives.